A comparative study of preoperative color‐coded Duplex ultrasonography versus handheld audible Dopplers in ALT flap planning. Issue 5 (5th May 2020) - Thomas, Benjamin; Warszawski, Jan; Falkner, Florian; Nagel, Sarah S.; Schmidt, Volker J.; Kneser, Ulrich; Bigdeli, Amir K.
Abstract: Introduction: The anterior lateral thigh (ALT) flap's vascular variability can lead to complications. Thus, the accuracy of numerous planning modalities has been studied. The clinical relevance of competing mapping methods, however, remains unknown. Therefore, we compared the impact of color‐coded Duplex ultrasonography and handheld audible Dopplers on surgical efficacy and flap safety. Patients and methods: Forty‐four ALT flaps were included in this comparative retrospective monocentric study. Twelve patients received Duplex scans and 32 flaps were designed using Dopplers only. Patient, defect, and flap characteristics of both groups were analyzed. The effect of either planning method on the primary outcome variables – flap harvest and operative times (HT, OT), course of perforator dissection, incidence of flap loss, emergent re‐explorations, and donor‐site revisions – was then assessed. Results: Patient, defect, and flap characteristics were comparable between both groups, including flap size (Doppler: 134 ± 73 cm 2, Duplex: 131 ± 65 cm 2, p = .90). There was no flap loss. Emergent re‐explorations (Doppler: 4/32, Duplex: 1/12, p = .70) and donor‐site revisions (Doppler: 2/32, Duplex: 1/12, p = .81) were equally distributed. Duplex rendered septal perforator dissection 10 times more likely (Chi‐Square = 8.9, p = .003, OR = 9.7), reaching 50% ( n = 6/12), as opposed to only 9% in the Doppler cohort ( n = 3/32). This allowed for highly significant HT and OT reductions of 89 minutes, respectively ( p < .01): from 255 and 383 min (Doppler) to 166 and 294 min (Duplex). Conclusions: Preoperative Duplex significantly reduces harvest and operative times of ALT flaps.